2018
DOI: 10.1016/j.cej.2018.04.065
|View full text |Cite
|
Sign up to set email alerts
|

Methanol oxidation in dry and humid air by dielectric barrier discharge plasma combined with MnO2–CuO based catalysts

Abstract: Presence of humidity in polluted gas streams is a key parameter to give a realistic view of a depollution process efficiency. With this in mind, the elimination of methanol by non thermal plasma in presence of a MnO2-CuO based catalyst and 35 % relative humidity (20°C, atmospheric pressure) was achieved. The reactor allows the treatment of low concentration pollutants (25-200 ppm) at weak residence time (0.36s) in air at atmospheric pressure. Based on conversion rate and CO2 selectivity, a 5 % MnO2/ 5 % CuO/ A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 38 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…Based on previous studies the depolymerization was achieved by reaction with active oxygen (ROS)/nitrogen (RNS) species. The slight increase of the reactor's temperature would lead to the release of water molecules from highly hygroscopic inulin and would enhance the formation of H 2 O 2 normalH2O+normalO·normalH2normalO2 …”
Section: Resultsmentioning
confidence: 99%
“…Based on previous studies the depolymerization was achieved by reaction with active oxygen (ROS)/nitrogen (RNS) species. The slight increase of the reactor's temperature would lead to the release of water molecules from highly hygroscopic inulin and would enhance the formation of H 2 O 2 normalH2O+normalO·normalH2normalO2 …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, other MnO 2 /metal oxides binary heterojunctions used for environmental purification have also been reported by researchers, including CuO/MnO 2 for the catalytic oxidation of acid fuchsin dye, [ 218 ] toluene, [ 219 ] methanol oxidation, [ 220 ] CO [ 221 ] and iopamidol; [ 222 ] MnO 2 /ZnO for the catalytic oxidation of Rhodamine B (RhB) [ 223 ] and tetracycline, [ 224 ] as well as MW absorption; [ 225 ] MnO 2 /Al 2 O 3 for the catalytic oxidation of toluene [ 226 ] and adsorption removal of Pb(II), [ 227 ] etc.…”
Section: Fabrication Of Mno2‐based Compositesmentioning
confidence: 99%
“…12 In order to reduce the yield of by-products in the process of removing low-temperature plasma generated by dielectric barrier discharge to remove VOCs and improve the reaction efficiency, a catalyst is usually used for the cooperative reaction. Studies [13][14][15][16][17][18][19][20] have shown that catalysts can effectively increase the reaction area, improve the removal efficiency of VOCs along with the selectivity of CO 2 , and reduce the formation of by-products. 21…”
Section: Introductionmentioning
confidence: 99%